2018
DOI: 10.1590/s0034-759020180104
|View full text |Cite
|
Sign up to set email alerts
|

Implementação Do Lean Healthcare: Experiências E Lições Aprendidas Em Hospitais Brasileiros

Abstract: This study aimed to analyze the process of implementing lean healthcare in three Brazilian hospitals that have played a pioneering role in the implementation of this system. We adopted the case study approach and collected data through interviews, document analysis, and observation. The results showed that the processes of implementation of lean healthcare in the hospitals shared many similarities in terms of the flow of patients, materials, or information. Finally, it was possible to obtain some guidelines fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
0
12
0
13
Order By: Relevance
“…As a management tool for the Care Unit, daily management was adopted, a method adapted from the Lean Model (10) , with active participation of nurses in order to expedite and monitor the patient's treatment including, in particular, monitoring the length of stay in the unit, according to the schedule made at admission. The method consists of extended multi-professional and daily visits by nurses, clinicians, surgeons, physiotherapists, social workers, pharmacists and nutritionists.…”
Section: Nsmm Care Process and Main Nursing Care Resultsmentioning
confidence: 99%
“…As a management tool for the Care Unit, daily management was adopted, a method adapted from the Lean Model (10) , with active participation of nurses in order to expedite and monitor the patient's treatment including, in particular, monitoring the length of stay in the unit, according to the schedule made at admission. The method consists of extended multi-professional and daily visits by nurses, clinicians, surgeons, physiotherapists, social workers, pharmacists and nutritionists.…”
Section: Nsmm Care Process and Main Nursing Care Resultsmentioning
confidence: 99%
“…Esses autores conseguiram observar a eliminação de 96% de processos desnecessários, diminuição do lead time do paciente em 84% e o aumento da quantidade de cirurgia em 10,6%. Régis et al (2017) examinaram a aplicação do Lean em 3 hospitais, localizados em São Paulo, e seus resultados, além da metodologia de aplicação, incluem a análise da filosofia implementada em mais de 10 setores de cada hospital. Os autores constataram a repetição do MFV, Kaizen e padronização.…”
Section: );unclassified
“…The results of these studies and in many other reviews (4,16,19,21,22) showed the processes of implementing Lean Healthcare had many similarities based on an understanding of the processes involved in flows of patients, materials or information. The most common tools were visual management, spaghetti map, time and motion studies, value stream mapping (VSM), Kaizen principles, standardization, (17,18,23) process mapping (11,24) and semi-structured interviews, documentary analyses and nonsystematic observations (23).…”
Section: Lean Principles and Tools Usage In The Healthcare Fieldmentioning
confidence: 99%